Notice of meeting - Morgan, Betty
040-0004-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMAN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: WILFRID ROBERTS, ESQ. M.P. LT.-COL. J.R.J. MACNAMARA. M.P. D.R. GRENFELL, ESQ M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD P.C. K.C. ORGANSING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, LONDON, S.W.1 TELEPHONE: SLOANE 9866 17th June 1939. There will be a meeting of the Basque Children's Committee on Thursday next, June 22nd, 1939, at 3.30 p.m. at the House of Commons, Room No.11. It is very much hoped that you will be able to attend. BETTY MORGAN Organizing Secretary. 292/946/40/4